2020
DOI: 10.3390/molecules25030659
|View full text |Cite
|
Sign up to set email alerts
|

Impact Mineralization of Chokeberry and Cranberry Fruit Juices Using a New Functional Additive on the Protection of Bioactive Compounds and Antioxidative Properties

Abstract: Chicken eggshells can be used as an attractive dietary source of mineral compounds, including calcium (Ca). However, the effects of chicken eggshell powder (CESP) on berry fruit juices have not been studied to date. Therefore, the objective of this study was to evaluate the effect of its addition to juices from chokeberry and cranberry on their phytochemical properties. The juices were determined for contents of polyphenols (determined by ultra-efficient liquid chromatography coupled with a mass detector (UPLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The fortification of muffins [102], yogurt [103], and soy milk jelly candy [104] with calcium derived from WCES powder improved the calcium content, protein content, shelf life, and general acceptability of the products. The impact of WCESderived calcium supplementation of beef sausage [105], chokeberry and cranberry fruit juices [106], and pizza and spaghetti [107], showed enhanced nutritional contents, better sensory attributes, and wider acceptability by the consumers when compared with unfortified products. The consensus among investigators showed a positive and encouraging outlook for calcium supplementation and fortification to meet the nutritional need of the consumers at a lower cost, using natural supplements.…”
Section: Application As Food For Human Consumptionmentioning
confidence: 98%
“…The fortification of muffins [102], yogurt [103], and soy milk jelly candy [104] with calcium derived from WCES powder improved the calcium content, protein content, shelf life, and general acceptability of the products. The impact of WCESderived calcium supplementation of beef sausage [105], chokeberry and cranberry fruit juices [106], and pizza and spaghetti [107], showed enhanced nutritional contents, better sensory attributes, and wider acceptability by the consumers when compared with unfortified products. The consensus among investigators showed a positive and encouraging outlook for calcium supplementation and fortification to meet the nutritional need of the consumers at a lower cost, using natural supplements.…”
Section: Application As Food For Human Consumptionmentioning
confidence: 98%
“…The antioxidative effects of polyphenols in berries to reduce age-related bone loss was reported by Hubert et al [ 62 ], indicating that berries are the possible cheap alternatives to reduce the risk of osteoporosis. Among the berries, the antioxidative effects of blueberry [ 63 , 64 , 65 ], chokeberry [ 66 , 67 , 68 , 69 ], cranberry [ 69 , 70 , 71 ], and goji berry [ 72 , 73 ] in reducing the risk of osteoporosis were reported. In recent years, new evidence has emerged of the health-promoting effects of sweat cherries on bone impairment associated with childhood obesity [ 74 , 75 ] demonstrated that obese children and adolescents bone impairment is sustained by spontaneous osteoclastogenesis, which can be limited in vitro by polyphenols presence.…”
Section: Bone and Osteoporosismentioning
confidence: 99%
“…The application of chicken eggshell powder in tannic acid-rich fruits, chokeberry and cranberry juice was once reported by Lachowicz et al [ 69 ]. In their article, they did not mention the inhibition of calcium absorption by tannic acid from chokeberry and cranberry, but they were concerned that the low pH in chokeberry and cranberry juice could increase the solubility of calcium from chicken eggshell powder, then afterward could increase the calcium absorption.…”
Section: Chicken Eggshell As Source Of Calcium and Its Applicationmentioning
confidence: 99%
“…In another application, they can be used as a nutritional additive in animal feed [ 3 , 4 , 13 ]. Moreover, because of their mineral content, especially calcium in a very easily bioavailable form, they can be used in the pharmaceutical industry to produce commercially available calcium supplements [ 4 , 10 , 13 , 22 ], and in the food industry as a source of dietary calcium in fortified food [ 23 , 24 ] or beverages [ 25 ]. In the available literature, we also found information about the preparation of eggshell powder at home and the selection of the correct amount for a natural calcium supplement [ 26 ].…”
Section: Introductionmentioning
confidence: 99%